PUSH AND PULL FACTORS OF INBOUND TOURISTS TO INDONESIA - HENDIJANI, Roozbeh Babolian (Journal of Environmental Management and Tourism, 2016)
Understanding the behavior of tourists has been an important topic of research for decades in tourism studies. A systematic study on the behavior of tourists visit to Indonesia, specifically the reason choosing this destination for vacation and also type of participated activities seek by different tourist groups, is lacking. Therefore, this study is undertaken to fill the gap by profiling the tourists and associating them with different tourism activities. A self-administrated questionnaire was distributed to tourists in Jakarta International airport and some tourist areas around Jakarta. Statistical analysis such as factor analysis, multiple linear regressions and descriptive analysis were employed in order to analyze the data. Results indicated the push factors behind choosing Indonesia for vacation and also different participated activities among tourists from different geographical origins. The findings of this study should be considered by tourism marketers and stakeholders while developing marketing strategies. Results also will have significant practical applications and theoretical implications.
Keywords: push factor; pull factor; overall satisfaction; Indonesia; inbound tourists